Perbedaan Tingkat Kecemasan Siswa Kelas III SMA di Denpasar Ditinjau dari Efikasi Diri dan Keikutsertaan dalam Bimbingan Belajar Menjelang Ujian Nasional - Dharmapatni, Putu Winda Yuliantari Gunapriya; Supriyadi, Supriyadi (Jurnal Psikologi Udayana; Vol 2 No 2 (2015), 2015)
Anxiety before the National Exam often perceived by third grade high school students. Anxiety not only affect physical condition, but also student learning activities in school when preparing the National Exam. This study aims to find level differences of third grade high school student’s anxiety in Denpasar in terms of self-efficacy and participation in tutoring before the National Exam Subjects are 266 third grade high school students in Denpasar which consists of students who join and not join tutoring. The instrument of this research are anxiety and self-efficacy scale that has been tested the validity and reliability of the scale, with Cronbach's alpha values anxiety scale=0.807 and Cronbach's alpha values of self-efficacy scale=0.758. Results of analysis covariance showed F=66.953;p<0.05, which means participation in tutoring and self-efficacy contributes to third grade high school students’s anxiety in Denpasar towards the National Exam. Differences in student’s anxiety based on participation in tutoring significantly indicates p=0.000 (p<0.05;F=17.578), which means that there’s differences in the level of anxiety among students who participate and didn’t participate tutoring. While the interaction of self-efficacy as covariance with anxiety has a significance of p=0.000 (p<0.05;F=116.123) this showed that self-efficacy significantly interact with anxiety. The contribution of self-efficacy and participation in tutoring to anxiety showed the adjusted R square 0.332 which means that self-efficacy and participation in tutoring can explain the varians anxiety of student by 33.2%. Results also showed that participation in the tutoring does not guarantee lower levels of student’s anxiety. Keywords: Anxiety, Third Grade High School Students, Self Efficacy, Opt in Tutoring